Mamoeiros ‘BOG’ e ‘BOS’: genótipos com porte reduzido como novas alternativas de cultivo - Malikouski, Renan Garcia (2019)
The papaya (Carica papaya L.) is one of the most important crops of the national agricultural scene and in the state of Espírito Santo, where the state is among the leaders in fruit production and productivity. This prominent position made it possible for companies in the branch to envision new farming systems and possible technologies to be inserted in the region. In order to obtain greater plant compactness, a cross was carried outs between the varieties Baixinho de Santa Amália and Golden Pecíolo Curto, genotypes derived from 'Sunrise Solo' mutations, characterized by low stature and reduced leaf petiole respectively. Among the genotypes obtained in the segregating generation F2, some of the characteristics of interest that were selected and cultivated for composition of the following generation, F2:3, were highlighted. These were inserted in two groups for leaf coloring, the Golden Ornamental Bauble (BOG), light green and Baixinho Ornamental Sunrise (BOS), dark green. Thus, the work divided into two chapters aimed to evaluate the progenies obtained by stating the stabilization of the vegetative characteristics that confer the reduction of the architecture of the plant and the viability of the cultivation of this material to a new technology proposed, the cultivation in pot. In the first chapter eight progenies of the cross were evaluated, together with the initial parents and a commercial variety, Golden THB. It was measured plant height, first fruit insertion height, petiole length, number of commercial fruits, as well as physico-chemical analyzes in fruits, such as length and width, mass, pulp firmness and soluble solids content. The non-parametric Kruskal-Wallis variance analysis was performed and the Student-Newman-Keuls test. The characteristics plant height, petiole length, fruit length and width stabilized in generation F2:3. Already number of commercial fruits, fruit mass, pulp firmness and soluble solids content require more generations of self-fertilization in order to stabilize. In the second chapter, the objective was to determine the dosage of the controlled release fertilizer and the polynomial mathematical growth model of the BOG papaya until the flowering phase, grown in pots, under the protected environment condition. Thus, the fertilizer called Basacote® Starter was applied in the doses of 25, 75, 125, 175 and 225 g per pot of 25 dm³ of volume in plants grown under greenhouse conditions. A completely randomized design was used in a plot of time split plot 5x8, 5 fertilizer doses and 8 evaluation periods, with 17 replicates each treatment and the experimental plot consisting of one pot. The following characteristics were evaluated: plant height; stem diameter; leaf area; chlorophyll index and at the end of the evaluations the dry mass of root and shoot was determined. The ideal dose of Basacote® Starter to full flowering was 123 g per pot. The growth curve for plant height as a function of time follows a third degree polynomial model, and for the leaf area and stem diameter characteristics, the appropriate polynomial model was the first degree.